Pengaruh Good Corporate Governance terhadap Integritas Laporan Keuangan dengan Moderasi Kualitas Audit pada Perusahaan Manufaktur di Indonesia - Erma Wulan Sari (Politeknik Ganesha Medan, 2026)
The integrity of financial statements is a crucial issue due to the potential for manipulation due to conflicts of interest and information asymmetry between management and owners. Research on the influence of Good Corporate Governance on the integrity of financial statements has shown inconsistent results.Most previous studies have focused on the direct influence of GCG on the integrity of financial statements,without considering contingency factors that could potentially strengthen or weaken the relationship. This study aims to examine the influence of corporate governance represented by independent commissioners,audit committees,and institutional ownership on the integrity of financial statements moderated by audit quality in manufacturing companies in the basic industry and chemical sub-sectors listed on the Indonesia Stock Exchange for the 2018-2022 period. This study employed 150 firm-year observations.The sampling method used purposive sampling. The analysis technique used multiple linear regression analysis and the Moderated Regression Analysis (MRA) test with IBM SPSS Statistics 25.The results showed that Independent Commissioners and audit committees influenced the integrity of financial statements,while institutional ownership had no effect.The moderating variable of audit quality moderates the influence of independent commissioners and institutional ownership on financial statement integrity. However,audit quality does not moderate the influence of the audit committee on financial statement integrity.This study strengthens the Good Corporate Governance literature by demonstrating that the effectiveness of GCG mechanisms in enhancing financial statement integrity depends not only on their existence but also on the quality of their implementation. These findings confirm that reducing agency conflicts requires synergy between internal and external mechanisms.